2019
DOI: 10.1021/acs.jnatprod.8b00753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biosynthetic Gene Cluster for the Antibiotic Armeniaspirols in Streptomyces armeniacus

Abstract: Armeniaspirols (1–3) are potent antibiotics against Gram-positive pathogens. Through a biosynthetic investigation, we identified four enzymes involved in the structural modification of 1–3. Manipulation of their activity led to the generation of 4–6 and nine novel analogues, 7–15. Bioactivity assessments revealed that the pyrrole chloro group and the methyl group are important for the antimicrobial activities of armeniaspirols, which lays the foundation for future structure optimization and mechanism of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Based on previous studies, armeniaspirols demonstrated no antimicrobial activity against many Gram‐negative bacteria (Couturier et al ., 2012 ; Qiao et al ., 2019 ). Thus, besides the cell membrane disrupting mode, we speculate there may also have alternative mechanisms for the bactericidal activity of armeniaspirole against H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies, armeniaspirols demonstrated no antimicrobial activity against many Gram‐negative bacteria (Couturier et al ., 2012 ; Qiao et al ., 2019 ). Thus, besides the cell membrane disrupting mode, we speculate there may also have alternative mechanisms for the bactericidal activity of armeniaspirole against H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Armeniaspirols, with a unique chlorinated spiro[4.4]non‐8‐ene scaffold (Table 1 ), are a new class of natural antibacterial products isolated from Streptomyces armeniacus (Couturier et al ., 2012 ). In our recent work, we identified four enzymes involved in the biosynthesis of armeniaspirol A‐C (1 − 3) isolated from S. armeniacus DSM 43125 and manipulated their activity to generate nine new analogues, 7–15 (Table 1 ) (Qiao et al ., 2019 ). Particularly, armeniaspirols 1–6 displayed potent activity against a range of multidrug‐resistant Gram‐positive bacterial pathogens, including Staphylococcus aureus , Enterococcus faecium and Bacillus subtilis (Couturier et al ., 2012 ; Dufour et al ., 2012 ; Qiao et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asukamycin contains a modified PKS scaffold and an electrophilic epoxide ring and has been shown to act as both a farsenyltransferase inhibitor and a molecular glue between the UBR7 E3 ubiquitin ligase and the TP53 tumor suppressor, leading to cell death (Hara et al, 1993;Isobe et al, 2020). Armeniaspirol contains a unique chlorinated pyrrole and inhibits the AAA+ proteases ClpXP and ClpYQ leading to cell division arrest in Gram positive bacteria (Labana et al, 2021;Qiao et al, 2019). The other two BGCs produce compounds of known structure but unknown function-tambromycin and JBIR-34/35 are similar NRPS compounds containing densely substituted chlorinated indole and methyloxazoline moieties (Muliandi et al, 2014).…”
Section: Characterized Bgcs Containing Alkz Homologsmentioning
confidence: 99%
“…Intriguingly, while we drafted this manuscript, Labana et al published the interaction of the 3 armeniaspirol derivative 4 with the proteases ClpXP and ClpYQ -a mechanism that is different to the ones we report below (see discussion). 9 In a first synthesis of armeniaspirols, 10 we have constructed the spiro- [4.4]non-8-ene scaffold through an attack of the phenolic group at C-8 of the benzoylated pyrrole ring, mimicking the presumed and later confirmed biosynthesis of the natural product 11,12 (Supplementary Scheme S1). The synthesis was short (7 steps, 13.8% overall yield), but the oxidative chlorination conditions led to chloroarmeniaspirol 4 rather than the natural product itself, as the chlorination at the pyrrole ring was inevitably associated with an undesired chlorination at the electron-rich C2 position.…”
Section: Introductionmentioning
confidence: 99%